Antecedents and Consequences of Wetland-Based Forensic Accounting in South Kalimantan: A Qualitative Study (Pusat Riset dan Inovasi Nasional, 2026)
Forensic accounting has become a global concern in facing increasingly complex economic and environmental challenges, particularly in detecting and preventing non-transparent financial practices, fraud, and misuse of resources. The concept of forensic accounting focuses on evidence-based financial investigations to uncover irregularities in asset management, including in sectors related to the wetland environment and sustainable economics. Amidst increasing concerns about climate change, environmental degradation, and natural resource exploitation, forensic accounting plays a crucial role in ensuring accountability and transparency in financial management, thereby supporting sustainable development policies more effectively. This study aims to evaluate the antecedents and consequences of the application of forensic accounting to economic, environmental, and social aspects, particularly in improving accountability, transparency, and mitigating financial risks. This study uses a qualitative approach with ethnographic methods, in-depth interviews, participant observation, and document analysis. The results show that antecedent factors include weak understanding of regulations, limited human resources, and limited data, while the consequences of the application of forensic accounting have a positive impact on the efficient use of public funds , strengthening governance, and improving social welfare. These findings are expected to be a foundation for policymakers in designing strategies for implementing forensic accounting that are more effective, inclusive, and sustainable in South Kalimantan